2014
DOI: 10.1182/blood-2013-07-517292
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lymphoma vascularization and dissemination by estrogen receptor β agonists

Abstract: Key Points Estrogen receptor β (ERβ) activation inhibits lymphoma growth, vascularization, and dissemination in vivo. ERβ activation may mechanistically explain differences in gender incidence and prognosis and contribute to new therapies of lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 51 publications
7
54
0
1
Order By: Relevance
“…Importantly, we reported an aberrant global DNA hypomethylation in BLM cells, indicative of genome instability; ERβ activation reverted this hypomethylation status (110). Taken together, these data demonstrate that, in NRAS-mutant melanoma cells, ERβ is associated with an antitumor activity, by causing cell cycle arrest and through the regulation of cell cycle-associated proteins; similar observations were previously reported in different types of cancers expressing this receptor (94, 101, 134140). Surprisingly, in our paper, we could also show that ERβ agonists were ineffective in reducing the proliferation of A375 and WM1552 (V600E BRAF-mutant) melanoma cells, expressing the ER isoform.…”
Section: Antitumor Activity Of Erβ In Melanomasupporting
confidence: 89%
“…Importantly, we reported an aberrant global DNA hypomethylation in BLM cells, indicative of genome instability; ERβ activation reverted this hypomethylation status (110). Taken together, these data demonstrate that, in NRAS-mutant melanoma cells, ERβ is associated with an antitumor activity, by causing cell cycle arrest and through the regulation of cell cycle-associated proteins; similar observations were previously reported in different types of cancers expressing this receptor (94, 101, 134140). Surprisingly, in our paper, we could also show that ERβ agonists were ineffective in reducing the proliferation of A375 and WM1552 (V600E BRAF-mutant) melanoma cells, expressing the ER isoform.…”
Section: Antitumor Activity Of Erβ In Melanomasupporting
confidence: 89%
“…A key role for ERβ in the inhibition of tumor growth in different forms of cancers has been hypothesized [10, 12, 25, 26]. In particular, a recent study carried out in breast cancer suggested that ERβ activation could inhibit cancer cell proliferation through a mechanism that bring into play a marked reduction of G2/M phase as well as triggering autophagy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERα exerts pro-proliferative effects, whereas ERβ activates an anti-proliferative signaling pathway through the execution of a specific and complex gene expression program [8, 9]. ERβ represents the main ER expressed in lymphoid malignancies while ERα levels are very low or undetectable [6, 1012]. ERβ activation by selective agonists was found to inhibit non Hodgkin lymphoma (NHL) growth, both in cell-based- and mouse-models, mainly reducing cell proliferation [10, 12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations